Economic effects of investment in mini digital solar dryer - Lana Nastić; Marko Jeločnik; Jonel Subić (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
In theory and practice, there comes to increase in focus to digitalization in agriculture, as well as about the rational use of available natural resources, primarily land, water and energy. The use of renewables, such is solar energy, can be done in various purposes, for example for energy supply of, among other income-generating activities, processing capacities at the farms. However, agriculture in Serbia is still largely performed in traditional way, without implementation of innovative solutions, or use of modern knowledge. Caused by that, the main goal of this research is to determine the economic effects of investing in establishment of mini digital dryer based on solar energy, which can be used for drying fruits, vegetables, medicinal herbs, spices and mushrooms. Research is based on real data obtained from the use of digital solar dryer implemented at experimental farm, while for investment analysis are applied usually used dynamic methods. Analysis has also considered assessing the impact of change in investment, value of inputs (plant based raw material), or price of final food products on the gained results of economic analysis. The analysis has indicated positive economic results of introduction of innovative drying system for agricultural products, whereby the economic effects of investment are sensitive the most to change in price of final food products.
Keywords: A10; C83; 330; investment; food processing; agricultural products drying; renewables; solar energy